Effect of different loading pistons on stress distribution of a CAD/CAM silica-based ceramic: CAD-FEA modeling and fatigue survival analysis - Miranda, Jean Soares [UNESP]; de Carvalho, Ronaldo Luís Almeida [UNESP]; de Carvalho, Rodrigo Furtado; Borges, Alexandre Luis S. [UNESP]; Bottino, Marco Antônio [UNESP]; Özcan, Mutlu; Melo, Renata Marques de [UNESP]; Souza, Rodrigo Othávio de Assunção e (Elsevier, 2019)
Purpose: This study evaluated the effect of different loading pistons, made of various materials and with different elastic moduli acting as antagonist material, on stress distribution and fatigue behavior of a CAD/CAM silica-based ceramic. Materials and methods: Discs of CAD/CAM made silica-based ceramic (N = 60) (VITA MARK II) were divided into six groups (n = 10 per group), according to the test method (M: Monotonic; F: Fatigue) and the antagonist piston material (T: Tungsten; S: Steel; G: Epoxy resin). FT, FS and FG combinations were submitted to mechanical cycling (2 × 10 6 cycles, 4 Hz, 45 N). The bending stress after fatigue were also valuated using Weibull analysis and the parameters η (eta), β (beta) and the mean time to failure (MTTF) were calculated. Fractographic analysis and Finite Element Analysis (FEA) were performed. Data were analyzed using ANOVA and Tukey's tests (alpha=0.05). Results: MG presented significantly less bending strength (MPa) (75.6) compared to MT (87.8) and MS (84.4) (p < 0.05). Six specimens from FT (MMTF: 8.3 × 10 6 ; β:0.60; η:5.6 × 10 6 ), four from FS (MMTF: 1.9 × 10 6 ; β:1.2; η:2.0 × 10 6 ) and one from FG (MMTF: 1.3 × 10 6 ; β:0.48; η:0.64 × 10 6 ) survived the fatigue test. The stress peak on the tensile surface of S was similar to that of T and both were less than that of G. The failure origins were on the tensile surface. Conclusion: The epoxy resin pistons were able to decrease the bending stress, and life expectancy (faster failure) of a silica-based ceramic compared to tungsten and steel.
Keywords: Bending stress; Biaxial flexural strength; Fatigue; Feldspar ceramic; Finite element analysis; Stress; Survival